Penetrating Export Markets through Local Products: A Case Study of Airafood SMEs in Indonesia - Rayyan Sugangga; Sudarmiatin Sudarmiatin; Puji Handayati (Greenation International Journal of Economics and Accounting, 2025)
This research aims to analyze the dynamics of Micro, Small, and Medium Enterprises (MSMEs) in penetrating the export market, focusing on strategies, challenges, and integration of social impacts in business operations. Using a descriptive qualitative approach with a hypothetical case study illustration on “Airafood Sejahtera Bersama,” an MSME in the food sector, this research examines how the principle of starting a business from a small and modest scale, as well as gradual internationalization theories such as the Uppsala Model, are relevant in the context of global market expansion by MSMEs. The discussion highlights the challenges faced, including compliance with international standards, market access, and limited resources, while identifying adaptive strategies such as product innovation, utilization of digital marketing, and network building. Furthermore, the study emphasizes the importance of creating shared value and implementing the Triple Bottom Line principle through social impact initiatives, such as empowering local women and farmers and responsible waste management, as crucial elements for the sustainability and increased competitiveness of MSMEs in international markets. In conclusion, the success of MSMEs in the global arena depends not only on product excellence and smart market strategies, but also on a commitment to business practices that are ethical, sustainable and make a positive contribution to the wider community.